(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Spatial distribution patterns along the Indian coastline, focusing on key regions such as the Sundarbans, Andaman and Nicobar Islands, Gulf of Kutch, Maharashtra, Gujrat and Odisha. Environmental factors, including salinity, tidal range, and sediment type, are discussed as critical influencers of mangrove composition and structure. Satellite imagery analysis, exemplified by Giri et al. (2011), reveals the impact of anthropogenic activities, such as coastal development and aquaculture, on mangrove cover over time. Conservation implications are highlighted, emphasizing the need for tailored initiatives that address specific threats faced by diverse mangrove ecosystems in India.